2012
DOI: 10.1037/a0025612
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety reactivity and anxiety perseveration represent dissociable dimensions of trait anxiety.

Abstract: Trait anxiety is an individual-difference variable reflecting variation in state-anxiety elevations resulting from exposure to a stressor. It is usually measured using questionnaire instruments, such as the Spielberger State-Trait Anxiety Inventory (STAI-T). The present research conceptually distinguishes, and independently assesses, two hypothetical dimensions of anxiety vulnerability which, it is argued, could plausibly make independent contributions to variance in trait-anxiety scores. These dimensions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
(35 reference statements)
2
29
0
Order By: Relevance
“…Rudaizky, Page, and MacLeod (2012) have recently demonstrated that anxiety reactivity, which reflects the elevated probability of an anxious reaction being elicited in response to a stressful situation, and anxiety perseveration, which reflects the increased tendency to experience prolonged anxious reactions to stressors, are dissociable dimensions of anxiety vulnerability. These researchers suggest that differing attentional mechanisms may underpin these two facets of anxiety vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Rudaizky, Page, and MacLeod (2012) have recently demonstrated that anxiety reactivity, which reflects the elevated probability of an anxious reaction being elicited in response to a stressful situation, and anxiety perseveration, which reflects the increased tendency to experience prolonged anxious reactions to stressors, are dissociable dimensions of anxiety vulnerability. These researchers suggest that differing attentional mechanisms may underpin these two facets of anxiety vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Stress-induced lack of control over automatic defensive responses is especially problematic for people in high-risk professions, such as police officers, whose control over automatic responses is essential for optimal performance under threat (Nieuwenhuys, Savelsbergh, & Oudejans, 2012). Moreover, difficulties controlling automatic defensive responses may not only affect split-second decisions under acute threat, but also increase the risk for development and persistence of posttraumatic stress disorder (PTSD) symptoms (Kozlowska, Walker, McLean, & Carrive, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While trait anxiety is commonly considered to be a unitary dimension of emotional temperament, recent research by Rudaizky, Page, and MacLeod (2012) suggests that it is possible to dissociate two different facets of anxious disposition that each account for independent variance in conventional trait anxiety scores, as measured by the STAI-T. One such dimension reflects individual differences in the intensity of a state anxiety reaction elicited by stressors, and this can be labeled as anxiety reactivity (AR). The other dimension reflects individual differences in the persistence of state anxiety elevations elicited by stressors, and this can be labeled as anxiety perseveration (AP).…”
mentioning
confidence: 98%
“…For example, Beck and Clark (1997) propose that the primary anxious response is underpinned by involuntary threat appraisal mechanisms that act rapidly and outside of conscious awareness, whereas the secondary anxious response is underpinned by deliberate and effortful cognitive processing of information associated with the particular stressor responsible for the initial elicitation of the anxious response. Rudaizky et al (2012) found evidence that these two dimensions of anxiety vulnerability can be dissociated through the use of a novel questionnaire measure. In this study, participants completed three separate scales: the standard STAI-T questionnaire, followed by an AR scale and an AP scale.…”
mentioning
confidence: 98%
See 1 more Smart Citation